2001
DOI: 10.1046/j.1365-2672.2001.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a bacteriocin-like compound (Lichenin) produced anaerobically by Bacillus licheniformis isolated from water buffalo

Abstract: Aims: To characterize a bacteriocin‐like factor from Bacillus licheniformis 26 L‐10/3RA isolated from buffalo rumen. Methods and Results: The culture supernatant exhibited the antibacterial activity against a number of indicator organisms in a cut‐well agar assay under anaerobic conditions. The inhibitory component was purified by following ammonium sulphate precipitation, gel filtration and ion exchange chromatography and confirmed to be a single peptide. A single band on tricine‐sodium dodecyl sulphate‐poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 31 publications
4
74
0
Order By: Relevance
“…HPLC indicated that the acidic NaCl extracts had some inactive peptides, but the active peptide could be purified and concentrated by rechromatography. The active peptide could not be silver stained, and other workers have noted a similar phenomenon (Carolissen-Mackay et al, 1997 ;Pattnaik et al, 2001 ;Villani et al, 1995). However, it reacted with Coomassie stain after the gel had been fixed with glutaraldehyde (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…HPLC indicated that the acidic NaCl extracts had some inactive peptides, but the active peptide could be purified and concentrated by rechromatography. The active peptide could not be silver stained, and other workers have noted a similar phenomenon (Carolissen-Mackay et al, 1997 ;Pattnaik et al, 2001 ;Villani et al, 1995). However, it reacted with Coomassie stain after the gel had been fixed with glutaraldehyde (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…(Table 1). The inhibitory spectrum of this substance is rather similar to that of some BLS, such as lichenin (Pattnaik et al, 2001), entomocin 9 (Cherif et al, 2003) and BLS P40 .…”
supporting
confidence: 51%
“…Most bacteriocins produced by Bacillus have a higher molecular weight, like thuricin 439A of 2,919.9 Da, thuricin 439B of 2,803.8 Da (Ahern et al, 2003), and subtilosin A of 3,398.9 Da (Stein, 2005). However, the molecular mass of this peptide was close to a lipopeptide antibiotic of 1,500 Da produced by B. subtilis EN 63-1 (Bechard et al, 1998) and lichenin produced by Bacillus licheniformis of 1,400 Da (Pattnaik et al, 2001). The cluster of peaks differing by 14 Da suggests the presence of a molecule containing a fatty acid chain of variable length (CH 2 ϭ14 Da).…”
mentioning
confidence: 98%
“…In vitro antagonistic activity of Bacillus cereus TC-1 against the five pathogenic Vibrio sp was tabulated in Table 2 Bacillus is an interesting genus to investigate for antimicrobial activity since Bacillus species production a diverse array of antimicrobial peptides representing several different basic chemical structures 23 , with a distinct diversity in their inhibitory activities against a variety of micro organisms 24 25 . Pseudoalteromonas sp.…”
Section: Resultsmentioning
confidence: 99%